Senior High School Students’ Perception of Using Microsoft Teams as A Platform for Learning English Reading - Desi Prihatin Kushandayani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Reading is a significant part of the educational process because it canimprove the students' abilities in English learning, such as increasing various newvocabulary, improving brain connectivity, thinking critically related to the content of the text, and gaining a lot of important information from what they read. Ontheother hand, Rahayu et al. (2022) stated that global access to information, together with recent technological advancements, has made a significant transitionfromprint to digital reading. It changes the reading behavior of students fromreadingwith printed materials to digital materials due to the use of the internet in reading, which gives wider access to various reading topics that could make readingmoreinteresting than traditional printed books (Rahayu et. al., 2022). To adapt tothat change, various schools also develop their learning process by using variousonline platforms, and one of the most popular learning platforms is Microsoft Teams. Hubbard & Bailey (2018) stated that Microsoft Teams could be treatedasone of the best applications that collaborate several different apps such as Office365 including Word/Excel/PowerPoint, Skype, Outlooks meeting, a persistent chat client, OneDrive for Business, a SharePoint site collection, schedulingsoftware, and Azure Active Directory (AAD) into one tool. Unfortunately, not all the students are ready to use Microsoft Teamsdirectly because of various reasons. Thus, in this research, the researcher wants toexplore the use of Microsoft Teams on reading skills because there are still few researchers who make observations on this topic at the high school level, especially in the Indonesian context. This research was aimed at investigating the students’ perceptions of usingMicrosoft Teams as a medium for teaching reading at the Senior High School. The researcher conducted this research at one of the senior high schools inProbolinggo, East Java, by applying a qualitative research design and using semi- structured interviews to collect the data. The participants of this research are6students who are randomly selected from various classes in that particular school. Then, the results of the obtained data were analyzed by using the thematicanalysis method. In short, based on the results of the obtained data, most students hadpositive perceptions of Microsoft Teams for reading. Most of themalso foundtheplatform helpful because it allowed them to access materials easily, repeat lessonsanytime, and learn at their own pace. However, some students also facedchallenges, including technical problems like slow notifications or heavyfiles, and confusion about how to use certain features.
Reuploud file repositori 6 Mei 2026_Firli Approved by Teddy
Keywords: Theory of Perception; Microsoft Teams; English Reading